Development of a High Jump Apparatus in High School - Rhoni Adi Arthama Hutagalung; Hari Adi; Rahma Dewi (UNIB Press, 2023)
The main objective of this research is to develop a high jump tool for senior high schools. This research was carried out at SMA Kristen Imenuel Medan Medan and will be held from August 6 to September 7 2022. The type of research used is Research and Development, with small group trial media experts reaching 88% in the valid category, media experts learning in small group trials reached 82% in the valid category, athletic experts in small group trials reached 87% in the valid category, and small group trials of 10 students reached 80% in the valid category, then large group trials of media experts reached 95%. In the valid category, the large group trial of learning media reached 90% in the valid category, the large group trial of athletic experts reached 95% in the valid category, and the large group trial of 30 SMA Kristen Immanuel Medan students reached 85% in the valid category. On the basis of the data obtained, the development of a high jump tool is declared valid or suitable for use as a medium for high jump learning in senior high schools.